Race and Ethnicity Predict Bone Markers and Fracture in Pediatric Patients With Chronic Kidney Disease. (23rd October 2020) - Laster, Marciana; Denburg, Michelle; Okuda, Yusuke; Kumar, Juhi; Furth, Susan; Warady, Bradley; Kalantar‐Zadeh, Kamyar; Norris, Keith; Salusky, Isidro B
ABSTRACT: Studies in healthy children have shown racial‐ethnic differences in bone markers and bone outcomes including fractures. At present, limited studies have evaluated the impact of race and ethnicity on bone markers and fractures within the pediatric chronic kidney disease (CKD) population. In a cohort study of 762 children between the ages of 1.5 years and 18 years, with CKD stages 1 to 4 from the CKD in children (CKiD) cohort, the relationship between racial‐ethnic group and bone markers (parathyroid hormone [PTH], 25‐hydroxyvitamin D [25‐OHD], 1, 25‐dihydroxyvitamin D [1, 25(OH)2 D], and C‐terminal fibroblast growth factor [FGF23]) was determined using linear mixed models. Additionally, logistic regression was used to evaluate racial‐ethnic differences in prevalent fracture upon study entry. Black race was associated with 23% higher PTH levels (confidence interval [CI], 2.5% to 47.7%; p = .03), 33.1% lower 25‐OHD levels (CI, −39.7% to −25.7%; p < .0001), and no difference in C‐terminal FGF23 or 1, 25(OH)2 D levels when compared to whites. Hispanic ethnicity was associated with 15.9% lower C‐terminal FGF23 levels (CI, −28.3% to −1.5%; p = .03) and 13.8% lower 25‐OHD levels (CI, −22.2% to −4.5%; p = .005) when compared to whites. Black and Hispanic children had 74% (odds ratio [OR] 0.26; CI, 0.14 to 0.49; p = .001) and 66% (OR 0.34; CI, 0.17 to 0.65; p < .0001) lower odds of any fracture than white children at study entry, respectively. Race and ethnicity are associated with differences in bone markers and despite lower 25‐OHD levels, both black and Hispanic children with CKD reported a lower prevalent fracture history than white children. The current findings in the CKD population are similar to racial‐ethnic differences described in healthy children. Additional studies are needed to better understand how these differences might impact the management of pediatric CKD‐MBD. © 2020 American Society for Bone and Mineral Research (ASBMR).